Dry Sliding Tribological Behavior of Brake Oil Conditioned Ceramic Matrix Composites Reinforced With Carbon Fabric - Kumar P.; Srivastava V.K. (My University, 2025)
Ceramic composites are extremely sensitive to the surrounding environment. Their tribological performance may degrade drastically if they are polluted by some external agent. The present article was aimed to investigate the unidirectional sliding characteristics of brake oil treated woven carbon-carbon (C/C), and carbon-carbon-silicon carbide (C/C-SiC) composites. The laminate orientation, surface conformity, normal load, and sliding velocity were varied. It was depicted that the quantity of oil absorbed by the composites depends on the laminate orientation. The decay rate in friction coefficient revealed that C/C composites are more prone to brake oil in comparison to C/C-SiC composites. The results showed that it is difficult to make an assumption regarding the wear and friction behavior of laminated composites in low conformity contacts concerning normal load and sliding velocity. However, friction coefficient increased with increment in sliding velocity and normal load, for non-conformal Hertzian contacts. The generation of friction film was arduous in the presence of absorbed oil. SEM analysis of worn surfaces revealed different surface morphology for low, and non-conformal contacts which depicted distinct tribological mechanisms. © 2021, Springer Nature B.V.